CD137 Regulates Bone Loss via the p53 Wnt/β-Catenin Signaling Pathways in Aged Mice - Han, Jiyu; Wang, Yanhong; Zhou, Haichao; Zhang, Yingqi; Wan, Daqian (Frontiers in Endocrinology, 2022)
Senile osteoporosis is a chronic skeletal disease, leading to increased bone brittleness and risk of fragile fractures. With the acceleration of population aging, osteoporosis has gradually become one of the most serious and prevalent problem worldwide. Bone formation is highly dependent on the proper osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) in the bone marrow microenvironment, which is generated by the functional relationship among different cell types, including osteoblasts, adipogenic cells and bone marrow stromal cells in the bone marrow. It is still not clear how osteoporosis is caused by its molecular mechanism. With aging, bone marrow is able to restrain osteogenesis. Finding the underlying signals that oppose BMSC osteogenic differentiation from the bone marrow microenvironment and identifying the unusual changes in BMSCs with aging are important to elucidate the mechanisms of senile osteoporosis. We used 3 gene expression profiles (GSE35956, GSE35957 and GSE35959) associated with osteoporosis. And a protein-protein interaction (PPI) network was also built to identify the promising gene CD137. After that, we performed in vivo experiments to verify its function and mechanism. In this experiment, we found that significant bone loss was observed in aged (18-month-old) mice compared with young (6-month-old) mice. The adipose tissue in bone marrow cavity from aged mice reached above 10 times than young mice. Combining bioinformatics analysis and vivo experiments, we inferred that CD137 might be involved in the p53 and canonical Wnt/β-catenin signaling pathways and thereby influenced bone mass through regulation of marrow adipogenesis. Importantly, osteoporosis can be rescued by blocking CD137 signaling in vivo. Our research will contribute to our understanding not only of the pathogenesis of age-related bone loss, but also to the identification of new targets for treating senile osteoporosis.